1971
DOI: 10.1111/j.1469-8986.1971.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Extraversion and Neuroticism in Orienting Response Habituation

Abstract: Twenty different consonant trigrams were presented individually to 38 observers in a standard OR habituation paradigm while the GSRs and BSRs were recorded. The observers were later categorized according to extraversion and neuroticism (anxiety) scores. All observers evidenced habituation in varying degrees to these dissimilar stimuli; however, the stable observers responded to more of the stimuli than did the neurotics. This basic neuroticism effect was modified by the extraversion factor as shown by response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Other studies using electrodermal measures only and low intensity stimulation found less consistant differences between high and low E scorers' rate of habituation (e.g. Coles et al, 1971;Sadler et al, 1971).…”
Section: Discussionmentioning
confidence: 90%
“…Other studies using electrodermal measures only and low intensity stimulation found less consistant differences between high and low E scorers' rate of habituation (e.g. Coles et al, 1971;Sadler et al, 1971).…”
Section: Discussionmentioning
confidence: 90%